2021
DOI: 10.26651/allelo.j/2021-52-1-1310
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rhizome extracts from invasive knotweed species Fallopia japonica and F. ×bohemica on radish seed germination and root growth of seedlings

Abstract: Japanese knotweed (Fallopia japonica) (Houtt.) Ronse Decr. and Bohemian knotweed (F. ×bohemica) (Chrtek and Chrtková) J. P. Bailey are invasive plants in Slovenia. We studied the effects of aqueous extracts [0.5 %, 1 %, 2 %, 5 % and 10 % (w/v)] from rhizomes of F. japonica and F. ×bohemica on the seeds of radish (Raphanus sativus) and examined the morphological and biochemical changes during germination and early growth of seedlings. Germination and early growth of radish were monitored 3, 5 and 7 days after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…As the radish roots showed relatively severe signs of stress, we here have further investigated the allelopathic potential of these knotweed extracts against radish seedlings after 3 days of germination, to detect the first signs of inhibition. Although various short-term exposure scenarios to knotweed extracts (Vrchotová and Šerá 2008;Moravcová et al 2011;Dolenc Koce and Šoln 2018;Šoln et al 2021a, 2021b and applications of individual phytochemicals (Fan et al 2010;Tucker Serniak 2016) have been studied previously, their influence has never been compared nor analysed in the same study. Therefore, we compared the effects of these knotweed extracts to those of their most abundant phenols, i.e.…”
Section: Chemoecologymentioning
confidence: 99%
See 2 more Smart Citations
“…As the radish roots showed relatively severe signs of stress, we here have further investigated the allelopathic potential of these knotweed extracts against radish seedlings after 3 days of germination, to detect the first signs of inhibition. Although various short-term exposure scenarios to knotweed extracts (Vrchotová and Šerá 2008;Moravcová et al 2011;Dolenc Koce and Šoln 2018;Šoln et al 2021a, 2021b and applications of individual phytochemicals (Fan et al 2010;Tucker Serniak 2016) have been studied previously, their influence has never been compared nor analysed in the same study. Therefore, we compared the effects of these knotweed extracts to those of their most abundant phenols, i.e.…”
Section: Chemoecologymentioning
confidence: 99%
“…Secondary compounds in knotweed rhizomes have been mainly analysed using various chromatographic techniques (Fan et al 2009;Chen et al 2013;Frantík et al 2013;Šoln et al 2021a) and mass spectrometry (Fan et al 2009). Xiao et al (2002) used NMR to structurally identify some new compounds from rhizomes of F. japonica from China.…”
Section: Nmr Analysis Of Knotweed Rhizomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Aqueous rhizome extracts of Japanese knotweed and Bohemian knotweed also delayed the germination of Raphanus sativus L., and suppressed their growth. The roots of R. sativus showed symptoms of oxidative stress such as abnormal shapes of nuclei, plasma membrane, mitochondria, and endoplasmic reticulum [ 56 , 57 ]. Aqueous rhizome extracts of Japanese knotweed ( Polygonum cuspidatum s.l.)…”
Section: Allelopathy Of Knotweedsmentioning
confidence: 99%
“…The root is of particular interest because it is a primary organ exposed to the direct influence of potentially harmful substances from the soil. Our previous studies (Dolenc Koce & Šoln, 2018;Šoln et al, 2021a; indicated that radish seedlings may be used as a model for studying root growth inhibition due to the robust morphology, rapid growth, and sensitivity to allelopathic compounds. We previously showed that in 7-day-old seedlings, extracts of F. japonica and F. Â bohemica rhizomes inhibited root growth by up to 65% and induced various biochemical changes related to oxidative stress ( Šoln et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%